2018
DOI: 10.1007/s10597-018-0301-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antidepressant Adherence at a Student-Run Free Mental Health Clinic

Abstract: Minority groups experience higher depression but lower treatment rates. Student-run free mental health (MH) clinics, such as the East Harlem Health Outreach Partnership (EHHOP) MH clinic, address this disparity. This study scrutinized EHHOP MH's depression treatment by measuring adherence to antidepressants. Pharmacy data from seventy-nine patients were reviewed according to HEDIS criteria. Results compare EHHOP MH to New York State (NYS) Medicaid and NYS commercial insurance providers. In the acute treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“… 51 By contrast, the more recent measured antidepressant medication adherence rates and found generally lower rates than in these comparison groups. 52 Another study, of a program attempting depression screening of all patients presenting to a SRC, diagnosed 19 previously undiagnosed cases of depression amongst 206 patients screened. Of patients with depression cared for in this clinic with two or more PHQ-9 tests at least four weeks apart, 57.1% saw clinically significant improvement.…”
Section: Resultsmentioning
confidence: 99%
“… 51 By contrast, the more recent measured antidepressant medication adherence rates and found generally lower rates than in these comparison groups. 52 Another study, of a program attempting depression screening of all patients presenting to a SRC, diagnosed 19 previously undiagnosed cases of depression amongst 206 patients screened. Of patients with depression cared for in this clinic with two or more PHQ-9 tests at least four weeks apart, 57.1% saw clinically significant improvement.…”
Section: Resultsmentioning
confidence: 99%
“…To conduct hypothesis-testing, we first retrieved data collected and published by the NYS DOH [ 23 – 25 ]. For the effective antidepressant medication management acute- and continuation-phase metrics, we also included our previously published data [ 15 ] in the comparisons to determine if the E-MHC’s performance improved over time. Due to the small sample size in our study and the unbalanced group sizes, Fisher exact tests were used to quantify the likelihood of patients having met the specific metric criteria between the E-MHC in 2019 and those from each of the comparator groups.…”
Section: Methodsmentioning
confidence: 99%
“…A study from the Yale-affiliated HAVEN clinic found that students could be trained to provide psychoeducation and lay counseling to depressed patients that led to symptom improvement [ 13 ]. Our clinic has reported preliminary evidence that an SRFC could provide clinical services for depressed patients that were as good as or superior to those rendered to patients enrolled in public health insurance programs [ 14 ]; however, a later report [ 15 ] documented lower rates of effective acute- and continuation-phase antidepressant treatment. While a follow-up study [ 16 ] indicated that on-site antidepressant dispensing may improve adherence rates, it is not known if this led to overall improvements in the number of patients meeting criteria for effective acute- and continuation-phase treatment long-term.…”
Section: Introductionmentioning
confidence: 99%
“…SRCs predominantly target the primary care needs of uninsured patients, with an emphasis on health care maintenance and chronic disease management (Smith et al, 2014 ). Several SRCs have offered mental health screening and care as increasing needs for these services are recognized (Batra et al, 2009 ; Doyle et al, 2012 ; Fischbein et al, 2020 ; Khonsari et al, 2019 ; Knoll et al, 2021 ; Liberman et al, 2011 ; Mann et al, 2019 ; Mishan & Dragatsi, 2017 ; Schweitzer & Rice, 2012 ; Soltani et al, 2015 ; Stuard et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To expand psychiatric services in primary care settings, some clinics have developed a model in which medication management occurs under the direct guidance of a consulting psychiatrist (Batra et al, 2009 ; Mishan & Dragatsi, 2017 ). SRCs have also begun to incorporate dedicated mental health treatment teams, allowing psychiatrists to work directly with medical students to provide medication management services with supportive interventions (Doyle et al, 2012 ; Khonsari et al, 2019 ; Knoll et al, 2021 ; Mann et al, 2019 ; Schweitzer & Rice, 2012 ; Soltani et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%